PENGARUH KOMUNIKASI, BUDAYA ORGANISASI, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Ni Luh Gede Putu Purnawati; Ida Ayu Nyoman Yuliastuti; Pande Ketut Ribek (Universitas Mahendradatta Denpasar, 2021)
A company will be able to run well if it creates a harmonious relationship in terms of good communication and is supported by a culture and a comfortable environment. This study aims to determine the effect of communication, organizational culture, and work environment on job satisfaction at Mizu Villa. The population used in this study were all employees who work at Mizu Villa, Kuta-Bali. Thus the total population is 30 people. Where the sampling technique used is a saturated sample method, namely the method of determining the sample using the entire population sampled in the study, so that the number of respondents used is 30 people. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that communication, organizational culture and physical work environment have a positive and significant effect on job satisfaction, meaning that the better communication occurs, the stronger the organizational culture is formed and the better the working conditions at Mizu Villa, the higher job satisfaction felt by employees